The role of financial investors in successful family-firm takeovers: A configurational approach - Nadine Kammerlander; Elias Kurta; Anne Heider (European Management Review, 2024)
Family firms increasingly opt for an external succession route and sell shares to financial investors. Yet, not all family-firm takeovers by financial investors are financially successful. To date, however, we lack a nuanced understanding of the conditions under which financial investors' family-firm takeovers will succeed financially. Our fsQCA study builds on 52 interviews to reveal the interplay of three typical levers that financial investors use (i.e., operational, strategic, and governance measures), the market situation, and investor type. We identify three distinct roles (i.e., incentivizers, optimizers, and adjacent investors) that financial investors take in successful family-firm takeover cases. We situate our findings in the literature on resources and their orchestration to explain how investors create value in each of the identified paths, and we contribute to the literature on family-firm succession and the interplay of family firms and financial investors.
Keywords: 650; family firms; financial investors; fuzzy-set qualitative comparative analysis; resources; takeover